2006
DOI: 10.1007/s11085-006-9023-0
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Mechanically Alloyed Al-rich Al–Ti Powders

Abstract: The oxidation behavior of Al-rich, metastable mechanically alloyed powders in the Al-Ti binary system has been examined in the context of their potential application in high-energy-density materials. Scanning calorimetry and thermogravimetric analysis in an oxygen atmosphere up to 1500°C have been performed on powders, synthesized with compositions ranging from Al 0.95 Ti 0.05 to Al 0.75 Ti 0.25 . Oxidation proceeds in three distinguishable steps, similar to the oxidation steps observed for pure aluminum. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…In addition, it is worth noting that no Al melting peak is observed, which is similar to the DTA results of mechanically alloyed Al–20Ti and Al–25Ti. 22 According to the XRD pattern of Al–20Mg–2Zr powder, most of Al has been alloyed with Mg and Zr to form intermetallic Al 3 Mg 2 and Al 3 Zr; the rest of pure Al is less, which results to the phenomenon of no Al melting peak in the DTA trace.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is worth noting that no Al melting peak is observed, which is similar to the DTA results of mechanically alloyed Al–20Ti and Al–25Ti. 22 According to the XRD pattern of Al–20Mg–2Zr powder, most of Al has been alloyed with Mg and Zr to form intermetallic Al 3 Mg 2 and Al 3 Zr; the rest of pure Al is less, which results to the phenomenon of no Al melting peak in the DTA trace.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the Al–Ti alloys were also investigated as fuels. 21,22 It was found that the ignition temperature of Al–Ti alloys reduced significantly, which concerned with the exothermic formation of the metastable L1 2 phase of Al 3 Ti. The burning rates of Al–Ti powder particles were faster than that of the same size Al particles.…”
Section: Introductionmentioning
confidence: 99%
“…Semenjak ditemukannya paduan Al-Ti, ternyata paduan ini telah dikenal sebagai salah satu bahan yang paling prospektif. Paduan ini dapat digunakan didalam industri luar angkasa dan berbagai kegunaan untuk peralatan mesin [2]. Paduan Al-Ti dapat juga diaplikasi pada suhu tinggi karena paduan ini antara lain memiliki ciri-ciri densitas yang rendah, titik lebur yang tinggi dan tahan terhadap korosi [3,4].…”
Section: Pendahuluanunclassified
“…One type of potential application for mechanically alloyed materials includes the use as metallic fuel additives for propellants, explosives, and pyrotechnics (Schoenitz and Dreizin, 2003Zhu et al, 2006;Chen et al, 2006;Zhu et al, 2007). Such materials are being developed to tailor the rates of energy release from the burning metal and thus improve performance of various energetic formulations.…”
Section: Chapter 5 Mechanically Alloyed Al-i Composite Materials Intmentioning
confidence: 99%